2016
DOI: 10.1155/2016/9704598
|View full text |Cite
|
Sign up to set email alerts
|

Heavy Cigarette Smokers in a Chinese Population Display a Compromised Permeability Barrier

Abstract: Cigarette smoking is associated with various cutaneous disorders with defective permeability. Yet, whether cigarette smoking influences epidermal permeability barrier function is largely unknown. Here, we measured skin biophysical properties, including permeability barrier homeostasis, stratum corneum (SC) integrity, SC hydration, skin surface pH, and skin melanin/erythema index, in cigarette smokers. A total of 99 male volunteers were enrolled in this study. Smokers were categorized as light-to-moderate (<20 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 72 publications
2
29
1
Order By: Relevance
“…Authors of this research attribute a high skin hydration on sebaceous gland-enriched sites (eg, forehead) of smokers to increased sebum production induced by nicotine. 39 In the same study, authors showed lower stratum corneum hydration on sebum-impoverished site (dorsal hand) of heavy smokers (≥20 cigarettes a day). Variations of measurements of skin hydration in our study and the study performed in Chinese population may also be due to the site of assessment and ethnicity.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Authors of this research attribute a high skin hydration on sebaceous gland-enriched sites (eg, forehead) of smokers to increased sebum production induced by nicotine. 39 In the same study, authors showed lower stratum corneum hydration on sebum-impoverished site (dorsal hand) of heavy smokers (≥20 cigarettes a day). Variations of measurements of skin hydration in our study and the study performed in Chinese population may also be due to the site of assessment and ethnicity.…”
Section: Discussionmentioning
confidence: 84%
“… 34 However, considering forearm as a sebum-impoverished site, our findings seem to be concordant with those from Chinese population study. 39 …”
Section: Discussionmentioning
confidence: 99%
“…Smoking cessation appears to be psychologically challenging while negatively impacting barrier recovery. Additionally, heavy, but perhaps not light‐to‐moderate, cigarette smoking can severely compromise epidermal barrier homeostasis …”
Section: Health Behavioursmentioning
confidence: 99%
“…Likewise, it has successfully been used to monitor the effects of different treatments on skin barrier function recovery (Sextius et al, 2010). Although TEWL has been reported to be affected by environmental factors such as temperature, seasonal variation, sun exposure, and smoking (Li et al, 2014;Liu et al, 2010;Xin et al, 2016), the presence of significant ethnic differences in stratum corneum permeability suggests that genetics also plays a role in epidermal barrier function (Kompaore and Tsuruta, 1993). However, to our knowledge, no genomic study has been conducted to explore the genetics of barrier function of healthy human skin.…”
mentioning
confidence: 99%